Effects of secondary fermentation of four in-bottle Saccharomyces cerevisiae strains on sparkling cider sensory quality. (August 2022) - Li, Wenting; Zhao, Yuning; Liu, Chen; Li, Shuai; Yue, Tianli; Yuan, Yahong
Abstract: In this study, the first fermentation of Fuji apple juice was carried out using Saccharomyces cerevisiae WLS21 and continued a second fermentation using S. cerevisiae HYJ1, HYJ2, PE2, and Y41 in sealed bottles after adjusting the sugar level. The physicochemical indexes, aromas, and sensory characteristics of four sparkling ciders were analyzed. The results revealed that HYJ2 produced the highest amount of ethanol and Y41 had the highest pressure in the bottle at the end of fermentation. Y41 produced the highest citric and succinic acids and HYJ1 produced higher fumaric acid and total volatiles. HYJ1 cider had an obvious herbaceous odor, and Y41 cider had a fruity character. Sixty-seven volatiles were detected from four sparkling ciders (55 fermentative and 12 non-fermentative aromas). Esters (EEFAs and HAAs) were the main volatile aroma family produced during secondary fermentation, and terpenes contributed the most to fruity odor. Based on univariate (ANOVA) and multivariate analysis of variance (PLS-DA) screening of four cider significant variables, 13 volatiles with variable predictive importance (VIP)≥1 were identified. PLSR analysis revealed that 2-methylbutyl acetate, ethyl heptanoate, 2-methyl-1-butanol, nonanal, 2-nonanone, β-damascenone, and linalool were potential volatile markers for OAV>1. Graphical abstract: Image 1 Highlights: S. cerevisiae strains affect the composition of sparkling cider. High variations of organic acids and ethanol were observed in sparkling ciders. Fruity aroma in cider from Y41 was from linalool and β-damascenone. Herbaceous aroma in cider from HYJ1 was from nonanal and 2-nonanone. Alcohol in HYJ2 cider had a negative effect on flavor.